2017
DOI: 10.4172/2375-4435.1000176
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic Factors of Dropout Situation in Rural Primary Education: A Study of Two Villages in Rajshahi District

Abstract: Dropout from school impedes development as it imposes human creativity and potentiality. It is the root of all backwardness. Rural communities are more backward particularly in Bangladesh, where the dropout rate is high. Parental decision to drop out their child from primary education does not depend upon gender but depend upon their economic status. Poverty influences the parents to withdraw their children from school. Studies on dropout in primary level, particularly Bangladesh, are inadequate however. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…These predictors constitute characteristics associated with the student and their personal environment that directly influence leaving the learning process unfinished. Ansary [49] identified student's age, gender, and land ownership pattern as significant predictors of study dropout in the leastdeveloped and developing economies. Prior research [41,42,47,48,[50][51][52][53][54][55][56][57] finds gender as an important predictor of university students' dropout.…”
Section: ) Personal (Student) Predictive Variablesmentioning
confidence: 99%
“…These predictors constitute characteristics associated with the student and their personal environment that directly influence leaving the learning process unfinished. Ansary [49] identified student's age, gender, and land ownership pattern as significant predictors of study dropout in the leastdeveloped and developing economies. Prior research [41,42,47,48,[50][51][52][53][54][55][56][57] finds gender as an important predictor of university students' dropout.…”
Section: ) Personal (Student) Predictive Variablesmentioning
confidence: 99%
“…According to Ansary (2017), household income is an important factor in determining access to education as schooling demands a range of costs including fees and other hidden costs such as uniforms, travel and up-keep. A related study done by Shahidul and Karim (2015) indicated that parents may not be able to support their children at school till completion of the programme due to socio-economic status such as poverty.…”
Section: Economic Factorsmentioning
confidence: 99%
“…Pilihan putus sekolah banyak dialami oleh anak-anak perempuan yang berasal dari keluarga miskin (Psacharopoulos & Patrinos, 2018 ;Mohan et al, 2018). Faktor lainnya disebabkan jumlah saudara kandung mereka banyak (T. Lestari & A. Setyadharma, 2019), anak-anak yang berada pada komunitas masyarakat pedesaan yang orang tuanya miskin dan tidak memiliki orientasi pada pendidikan anak-anaknya (Ansary, 2017), mereka juga dibebankan pada biaya sekolah (Kim, Donggeun & Kim, Seoyong, 2018), dan latar belakang budaya keluarga "kelas sosial" sebuah keluarga akan menjadi pembentuk cara pikir dan karakteristik psikologi seseorang yang malas, tidak memiliki semangat sekolah (Ghignoni, 2017). Demikian, dapat dipahami bahwa keputusan tidak lanjut sekolah ini akan membawa pada risiko tertentu.…”
Section: Pendahuluanunclassified
“…Faktor kondisi ekonomi keluarga menjadi faktor utama anak putus sekolah. Dimana kondisi ekonomi yang rendah (Ansary, 2017) Pada penelitian juga ditemukan bahwa orang tua memiliki andil penting dalam pendidikan anak, dimana tingkat pendidikan anak salah satunya dipengaruhi oleh pemikiran orang tua. Jika orang tua tidak memiliki pemikiran yang terbuka, tidak mau menerima perkembangan yang ada, maka kesadaran akan pendidikan terhadap anak-anak mereka juga kurang.…”
Section: Hasil Dan Pembahasanunclassified